04.12 The lymphatic system: a gatekeeper for migration of pathogenic t-cells towards synovial joints and entheses in psoriasis. (1st March 2017) - Bisoendial, Radjesh J; Prens, Errol P; Mus, Adriana MC; Asmawidjaja, Patrick S; Davelaar, Nadine; Hofman, Arien; Jaquet, Jean-Bart; Hazes, Johanna MW; Kok, Marc R; Lubberts, Erik
Abstract : Background: Psoriasis (PsO) is a common inflammatory skin disease that is characterised by acanthosis, impaired immune cell migration, and remodelling of the vascular and lymphatic system. Up to 30% of PsO patients develop psoriatic arthritis (PsA). The factors that determine the transition from PsO to PsA or vice versa are poorly understood. The lymphatic system may regulate the homing capabilities of disease- associated T-cells and control their migration to skin and extra-cutaneous sites like synovial joints and entheses. Methods: Human dermal lymphatic endothelial cells (LEC; 0.5 × 10 4 ), and fibroblast-like synoviocytes of a patient with PsA (PsA-FLS; 1.0 × 10 4 ) were pre-incubated for 3 days with PsA synovial fluid (PsA-SF; 0/10/20% v/v). Then, LEC or PsA-FLS were co-cultured with 2.5 × 10 4 allogeneic CD4+CD45RO+CD25- T-cells that were sorted from peripheral blood mononuclear cells (PBMC) of 3 healthy donors with or without stimulation with αCD3 (0.3 µg/ml) and αCD28 (0.4 µg/ml). After 72 hour, T-cells from duplicate wells were pooled and immunophenotyped by flow cytometry on a 4-laser LSR-II analyzer using antibodies directed to CD25, CD4, CD45, CD45RO, CXCR3, CCR4, CCR6, and CCR10. Based on the latter four, the most relevant T-helper (Th) subsets were characterised, including the CCR6+ subsets Th17.1 (CCR4-/CXCR3+), Th17/Th22 (CCR4+/CXCR3-), Th17 (CCR4+/CXCR3-/CCR10-) and Th22 (CCR4+/CXCR3-/CCR10+), and CCR6- subsets Th1 (CCR4-/CXCR3+), and Th2 (CCR4+/CXCR3-). We also looked at cutaneous lymphocyte- associated antigen (CLA), a skin homing receptor. IL-17A, IL-22, and TNF protein levels in the co-cultures were determined by ELISA. Statistical analysis included unpaired t-test (two-sided) for comparison between two groups or one-way ANOVA with the Tukey-Kramer post hoc test for multi-group comparisons. Results: Stimulation of CD4+CD45RO+ T-cells in co-culture with PsA-FLS skewed towards the CCR6+ subset Th17/Th22, which were predominantly Th17 cells. Th17 differentiation upon stimulation was suppressed in co-culture with LEC even when the LECs were pre-incubated with PsA-SF. Stimulation of CD4+CD45RO+ T-cells in co-culture with LEC, as compared to PsA-FLS, promoted the generation of the Th22 subpopulation. Upon co-culture with untreated LEC, stimulated CD4+CD45RO+ T-cells showed higher expression of the skin homing receptor CLA than those that were co-cultured with PsA-FLS. The proportional reduction in CLA expression on CD4+CD45RO+ T-cells in the co-cultures with LEC pre-incubated with PsA-SF 20% was equal to that in the co-cultures with PsA-FLS. However, these activated LEC conserved CLA expression at a higher level than PsA-FLS. This phenomenon that activated LEC conserved CLA expression on CD4+CD45RO+ T-cells particularly affected the CCR6+ T-cell subset. In line with FACS results, a trend towards lower IL-17A and higher IL-22 levels were observed in the co-cultures with LEC that were pretreated with PsA-SF 20%, as compared to the co-culture with PsA-FLS. No differences were seen for TNF protein levels. Conclusion: LECs are directly involved in T-cell differentiation, and homing capabilities, as shown by suppression of Th17 differentiation upon CD3/CD28 stimulation in co-culture experiments, as compared to PsA-FLS. In addition, LEC promoted Th22 generation, and conserved CLA expression in the CCR6+ T-cells subset, when LEC were preincubated with PsA-SF. Future studies: Studies are underway to show that LECs derived from other relevant biological tissues, including synovium, lymph nodes, and entheses are critical for inducing tissue-imprinting (chemokine) receptors at the time of T-cell activation, and for tissue-restricted migration to skin, synovial joints and entheses in PsO and PsA. A direct effect of LECs on the functional homing properties of these T-cells will be studied in 3D T-cell migration assays, including the crawl-in assay where increased entry into the lymphatic system can be studied